2021
DOI: 10.1177/10748407211001559
|View full text |Cite
|
Sign up to set email alerts
|

An Integrative Review of Experiences Parenting Transgender and Gender Diverse Children

Abstract: Transgender and gender diverse (TGD) children face increased behavioral health risks including suicidal behaviors and substance abuse. Parental affirmation is associated with behavioral health outcomes similar to non-TGD peers. This integrative review synthesizes and appraises evidence regarding experiences of parenting a TGD child in the United States or Canada from 2008 to 2018. Most parents across these 15 studies described affirming their child’s gender at time of interview. Parents reported initial interp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 82 publications
(253 reference statements)
0
6
0
Order By: Relevance
“…Longitudinal research that employs both parent and adolescent reports would also enhance our understanding of the reciprocal influence between parents and their adolescents. Research with LGBQTI + adolescents indicates that in well-functioning families, there is a shift from parental confusion and negativity at initial disclosure of LGBQTI + identity, to eventual acceptance and support of the young person (Warner et al, 2021 ). Thus, within a warm, connected and supportive parent-adolescent relationship, the adolescent has the potential to shift strongly held values about gender identity (and sexual orientation) in their parents.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Longitudinal research that employs both parent and adolescent reports would also enhance our understanding of the reciprocal influence between parents and their adolescents. Research with LGBQTI + adolescents indicates that in well-functioning families, there is a shift from parental confusion and negativity at initial disclosure of LGBQTI + identity, to eventual acceptance and support of the young person (Warner et al, 2021 ). Thus, within a warm, connected and supportive parent-adolescent relationship, the adolescent has the potential to shift strongly held values about gender identity (and sexual orientation) in their parents.…”
Section: Discussionmentioning
confidence: 99%
“…For both gender conforming and non-conforming LGBTQI + adolescents, gendered parenting and gender-typical expectations may be perceived as parental rejection (Mills-Koonce et al, 2018 ), which has been found to have a range of negative emotional and behavioral outcomes for adolescents (Ali et al, 2015 ). For gender non-conforming adolescents, gendered parenting may result in transgender or gender non-conforming adolescents not being ‘allowed’ to present in accordance with their internally felt gender (Warner et al, 2021 ). Support for an adolescent’s desired presentation (including their appearance, pronouns, name) may be an issue both for adolescents who do not identify with the gender they were assigned at birth, and for those who do not feel comfortable with a ‘standard’ gendered appearance (e.g., clothing style, use of makeup etc.…”
Section: Gendered Parenting Of Lgbtqi + and Gender Non-conforming Ado...mentioning
confidence: 99%
See 2 more Smart Citations
“…Parents' first reactions to their child's transsexualism are associated with concerns. They try to get information about this issue [7]. Mothers are always exposed to secondary stigma related to their children due to having transsexual children [8].…”
Section: Introductionmentioning
confidence: 99%